Will neuroscience ever enter the courtroom? - Olajossy-Hilkesberger, Luiza; Olajossy, Marcin (Current Problems of Psychiatry, 2012)
Advances in research into the neurobiological determinants of the human mind have raised questions concerning the factors underlying moral judgement and responsibility. The present work addresses both neuroscientific and legal issues and analyses the results of studies on brain structure and function in conditions such as psychopathy, paedophilia and aggressive behaviour. The associations between the existing nervous system abnormalities and the nature and type of the crime committed are discussed, as is the culpability of the perpetrator. The authors also address cost restrictions, which prevent more extensive use of fMRI in forensic psychiatry. fMRI data have already been used in the legal process and could be applied to establish the prognosis of aggressive behaviour and in simulation and long-term abstinence testing.